Poizkus opredelitve celovitejšega pristopa pri nadaljni informatizaciji upravnih enot v Sloveniji - Vintar, Mirko (Uporabna informatika (Ljubljana), 1996)
Informatization of public administration, which has been taking place in Slovenia in the last few years, has reached the level, when only introduction of new information and communication technology is barely enough. At this stage, we should focus on the organisational aspects of this process, if we want to take all advantages of this new technology for making public administration more efficient and its services of higher quality. In this article, main objectives and some starting-points of further informatization of public administration are presented and basic functional modules of integrated information system described.
Keywords: informacijska tehnologija; informatizacija; javna uprava; organizacija; Slovenija; upravne enote